Significance of bone biomarkers determination in the assessment of fracture risk and response to therapy in patients with osteoporosis - Milić Anđelka; Đurić Milena; Gajić Gordana; Mitrović Milan; Urošević Ljiljana; Jovanović Veljko; Ješić Budimir; Kovačević Radmila; Vekić Jelena; Zeljković Aleksandra; Stefanović Aleksandra; Ninić Ana; et al. (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2017)
Osteoporosis is characterised by reduced bone mineral density (BMD), increased bone fragility and risk of fractures. We investigated clinical significance of bone turnover biomarkers determination for the prediction of fracture risk and response to therapy. We performed three months follow-up study in 48 women with osteoporosis. During the follow-up period 32 patients were on antiresorptive and 16 patients received anabolic therapy. Serum alkaline phosphatase (ALP), osteocalcin, C-terminal telopeptide of collagen type I and vitamin D were measured before and 3 months after initiation of the therapy. Higher osteocalcin and ALP levels were significantly associated with increased risk of BMD loss. Following antiresorptive therapy levels of C-terminal telopeptide (P<0.001) and osteocalcin (P<0.001) significantly decreased. Anabolic therapy significantly increased osteocalcin (P<0.01). At the study entry 25.5% of the patients had optimal levels of 25(OH)D and 17% had severe vitamin D deficiency. Vitamin D supplementation during three months improved vitamin D status of the patients (P<0.001). In conclusion, our data indicate that osteocalcin and C-terminal telopeptide determination may be useful for BMD loss prediction and monitoring of osteoporosis therapy. This study confirmed importance of vitamin D testing in osteoporosis in order to detect the patients with deficiency and determine the need for supplementation.